Memantine versus Ginkgo biloba Extract: A Comparative Study on Cognitive Dysfunction Treatment in a Novel Rat Model - Allam, Essmat A. H.; Assi, Abdel-Azim; Badary, Dalia M.; Farrag, Magda M. Y.; Nicola, Mariam A. (Planta Medica, 2024)
Extracellular senile plaques and intraneuronal neurofibrillary tangles are two devastating brain proteinopathies that are indicative of Alzheimerʼs disease, the most prevalent type of dementia. Currently, no effective medications are available to stop or reverse Alzheimerʼs disease. Ginkgo biloba extract, commonly referred to as EGb 761, is a natural product made from the leaves of the G. biloba tree. It has long been demonstrated to have therapeutic benefits in Alzheimerʼs disease. The current study assessed the beneficial effects of EGb 761 against Alzheimerʼs disease in comparison with memantine, a standard treatment for Alzheimerʼs disease. The scopolamine-heavy metals mixture rat Alzheimerʼs disease model is a newly created model to study the effects of EGb 761 oral therapy on cognitive performance and other Alzheimerʼs disease-like changes over a 28-day experimental period. This new Alzheimerʼs disease model provides better criteria for Alzheimerʼs disease hallmarks than the conventional scopolamine model. The EGb 761 reversed memory and learning deficits induced by the scopolamine-heavy metals mixture. These outcomes were linked to a more pronounced inhibitory effect on acetylcholinesterase, caspase-3, hippocampal amyloid-beta protein (Aβ1 – 42), phosphorylated tau protein counts, and proinflammatory cytokines (tumor necrosis factor-α and interleukin-1β) compared to the memantine-treated group. Furthermore, EGb 761 treatment considerably reduced lipid peroxidation (malondialdehyde) and improved reduced glutathione levels compared to memantine. Our results suggest EGb 761′s potential in treating central nervous system disorders. Itʼs a promising candidate for future Alzheimerʼs disease therapeutic exploration. This study also highlights the need for future research to focus on the positive benefits of herbal medicines.
Keywords: Alzheimerʼs disease; Ginkgo biloba; EGb 761; Ginkgoaceae; scopolamine; heavy metals mixture; cytokines; oxidative stress